2010
DOI: 10.1002/ijc.25587
|View full text |Cite
|
Sign up to set email alerts
|

A water soluble parthenolide analog suppresses in vivo tumor growth of two tobacco‐associated cancers, lung and bladder cancer, by targeting NF‐κB and generating reactive oxygen species

Abstract: Dimethylaminoparthenolide (DMAPT) is a water soluble parthenolide analog with preclinical activity in hematologic malignancies. Using non-small lung cancer (NSCLC) cell lines (A549 and H522) and an immortalized human bronchial epithelial cell line (BEAS2B) and TCC cell lines (UMUC-3, HT-1197 and HT-1376) and a bladder papilloma (RT-4), we aimed to characterize DMAPT's anticancer activity in tobacco-associated neoplasms. Flow cytometric, electrophoretic mobility gel shift assays (EMSA), and Western blot studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 42 publications
0
50
1
Order By: Relevance
“…DMAPT is a water-soluble analogue of parthenolide, an active ingredient of the herb feverfew (22,27). As with many targeted therapies, DMAPT displays NF-κB-dependent and NF-κB-independent activities; however, its major therapeutic effects are likely through NF-κB inhibition (22).…”
Section: Resultsmentioning
confidence: 99%
“…DMAPT is a water-soluble analogue of parthenolide, an active ingredient of the herb feverfew (22,27). As with many targeted therapies, DMAPT displays NF-κB-dependent and NF-κB-independent activities; however, its major therapeutic effects are likely through NF-κB inhibition (22).…”
Section: Resultsmentioning
confidence: 99%
“…Despite widely documented anti-cancer activity and the absence of major adverse effects, clinical development of parthenolide is hampered by its poor water solubility, (35) thus limiting its potential as a promising clinical agent. Previous studies investigated the in vitro and in vivo activities of the water-soluble parthenolide analogue dimethylaminoparthenolide (DMAPT) (20,35,36) and reported that this analogue suppressed tumor growth by targeting NF-κB and generating reactive oxygen (37)(38)(39). The water-soluble parthenolide analogue may become a more readily available radio-sensitizing agent, but further investigation is needed to elucidate its efficacy and spectrum as a radio-sensitizing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic experiments using both mouse xenograft models and spontaneous acute canine leukemias demonstrated its high in vivo bioactivity (Guzman et al 2007). Further in vivo studies demonstrated that DMAPT significantly suppressed the growth of prostate (Shanmugam et al 2010), lung, bladder (Shanmugam et al 2011), and breast cancers (D'Anneo et al 2013). Moreover, it inhibited metastasis in mouse xenograft model of breast cancer and enhanced survival of the treated mice.…”
Section: Parthenolide-the Most Studied Sesquiterpene Lactonementioning
confidence: 93%